Recommendations for Management of Whiteflies, Whitefly-Transmitted Viruses, and Insecticide Resistance for Production of Cucurbit Crops in Florida - Xavier Martini; Mathews Paret; Jane E. Polston; Scott Adkins; Pamela Roberts; Teresia Nyoike; Oscar E. Liburd (EDIS)
This publication lists and describes common viruses spread in cucurbit crops by whiteflies. It includes strategies for managing whiteflies, most of them originally from a similar publication on managing whiteflies in tomatoes.